Referring to judo's sports injuries in São Paulo State Championship - Souza, M.; Monteiro, H.; Del Vecchio, F.; Goncalves, A. (Elsevier B.V., 2006)
Objective. - In a pioneer way, we investigated the morbidity of sports injuries referred by judo athletes from São Paulo State Championship.Material and methods. - Data collection from 93 senior judokas in State of São Paulo Judo Championship, through Referred Morbidity Inquiry about last year.Results. - One hundred and ten events were registered with a distribution frequency gradient of sprain > contusion > strain > ligament injury > partial and total dislocation. The most injured body areas were: knee (26.3%), shoulder (21.8%), fingers (17.3%), and ankle (10.0%). The most risky situation was when the athlete was training (standing, applying a blow) and it can be explained by the frequent and unprepared exposition of the athletes. Yearly lesion rate was 1.18 injuries per athlete/year.Conclusion. - Sprains constitute the most common judo injury, and athletes are more susceptible when they apply blows; discussion about the direction that the prevention should be applied remains opened. (c) 2006 Elsevier Masson SAS. All rights reserved.
Keywords: athletic injuries; martial arts; morbidity